2006
DOI: 10.1371/journal.pbio.0040145
|View full text |Cite
|
Sign up to set email alerts
|

Climate, Deer, Rodents, and Acorns as Determinants of Variation in Lyme-Disease Risk

Abstract: Risk of human exposure to vector-borne zoonotic pathogens is a function of the abundance and infection prevalence of vectors. We assessed the determinants of Lyme-disease risk (density and Borrelia burgdorferi-infection prevalence of nymphal Ixodes scapularis ticks) over 13 y on several field plots within eastern deciduous forests in the epicenter of US Lyme disease (Dutchess County, New York). We used a model comparison approach to simultaneously test the importance of ambient growing-season temperature, prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
443
6
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 419 publications
(487 citation statements)
references
References 58 publications
28
443
6
10
Order By: Relevance
“…Only in areas with only Roe deer did we find a correlation between the relative abundance of Roe deer and larval I. ricinus density. These results agree with a study on I. scapularis in which large variation in deer density did not result in changes in questing nymphal density, while there was a weak correlation with larval density 204 . Such a threshold relationship was already suggested by Wilson et al 202 and can explain equivocal effects of deer culling on densities of ticks in the I. ricinus complex 193 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Only in areas with only Roe deer did we find a correlation between the relative abundance of Roe deer and larval I. ricinus density. These results agree with a study on I. scapularis in which large variation in deer density did not result in changes in questing nymphal density, while there was a weak correlation with larval density 204 . Such a threshold relationship was already suggested by Wilson et al 202 and can explain equivocal effects of deer culling on densities of ticks in the I. ricinus complex 193 .…”
Section: Discussionsupporting
confidence: 91%
“…Which factors determine parasite load is of key interest in disease ecology and animal health, as many parasites negatively affect the condition of the host or vector pathogens. An increase in vector burden will potentially increase the number of hosts infected with a vector-borne pathogen and subsequently the number of infected vectors in the environment 33 , which is directly related to disease risk 204 . For parasites that are encountered in the environment, parasite burdens on hosts are determined by three factors: 1) the number of parasites in the environment, and 2) the day range of the host, which together determine the encounter rate of parasites and hosts 12 , and 3) the resistance or tolerance of hosts towards the parasite 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Disease ecology explores comprehensively how changes in a whole suite of factors such as population dynamics, movement, physiological state, species richness, and relative abundance of species within an ecological community can alter risks of exposure to infectious diseases (49,50). Recently, disease ecologists have shown that the risk of West Nile virus exposure in the United States rises as avian biodiversity falls (51,52), and, similarly, Lyme disease exposure increases with falling mammalian diversity (53)(54)(55). In field experiments, exposure to hantavirus increases when mammalian diversity falls (56).…”
Section: Highlights Of the Recent Literaturementioning
confidence: 99%
“…These findings are consistent with results from the eastern United States, where a PCR-positive eastern chipmunk (T. striatus) was reported from Minnesota (Walls et al 1997). In addition to maintaining active infection, chipmunks in the eastern United States support tick numbers, with a strong correlation between chipmunk numbers and the density of nymphal deer ticks one year later (Ostfeld et al 2006).…”
Section: Introductionmentioning
confidence: 99%